Determinasi Tingkat Pengangguran Terbuka di Kabupaten/Kota Provinsi Jawa Timur Tahun 2022 –2024 - hamda el ramadani poetra; Muthia Rahma Fadhilah (Universitas Negeri Surabaya, 2025)
This study analyzes the effect of Regional Gross Domestic Product (RGDP), Human Development Index (HDI), and Regional Minimum Wage (UMR) on the Open Unemployment Rate (TPT) in districts/cities in East Java Province during the period 2022–2024. The study uses secondary data from the Central Statistics Agency (BPS) and the Ministry of Manpower with a panel data regression method. The model selection was carried out through the Chow Test, Lagrange Multiplier (LM) Test, and Hausman Test, which consistently showed that the Fixed Effect Model (FEM) was the best model. The FEM estimation results with robust standard error show that GRDP and minimum wage have a negative and significant effect on TPT, while HDI has a negative but insignificant effect. The regional status variable was not estimated in the model because it is time-invariant. The R-squared value of 0.593 indicates that the model is able to explain 59.3% of the variation in TPT. These findings indicate the importance of economic growth, effective wage policies, and improving the quality of human resources relevant to labor market needs in efforts to reduce unemployment in East Java.